2014
DOI: 10.1584/jpestics.d13-076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel repellent, acetylated glyceride, against sweet potato whitefly, <i>Bemisia tabaci</i> (Gennadius) (Hemiptera: Aleyrodidae)

Abstract: With the aim of identifying safe control agents for whiteflies, we screened foods and food additives and observed that acetylated glyceride showed strong repellent activity against the sweet potato whitefly Bemisia tabaci. The acetylated glyceride (acetic and fatty acid esters of glycerol) has been used as food additives worldwide. The numbers of settled adults, courting pairs, and nymphs on host plant leaves were reduced by acetylated glyceride treatment. The highest control was attained with foliar treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…After adult whiteflies landed on the treated host leaves, they were not able to conduct normal mating behaviours during the remaining 4 days. The observed residual efficacy of acetylated glyceride was consistent with the finding that high control of B. tabaci B was achieved in field studies by applying foliar treatment (0.2%, v/v) at 7-day intervals (Kashima et al 2014).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…After adult whiteflies landed on the treated host leaves, they were not able to conduct normal mating behaviours during the remaining 4 days. The observed residual efficacy of acetylated glyceride was consistent with the finding that high control of B. tabaci B was achieved in field studies by applying foliar treatment (0.2%, v/v) at 7-day intervals (Kashima et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…The observed residual efficacy of acetylated glyceride was consistent with the finding that high control of B. tabaci B was achieved in field studies by applying foliar treatment (0.2%, v/v) at 7‐day intervals (Kashima et al. ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…After successive foliar treatments with 0.2% (v/v) acetylated glyceride 2 or 3 times at 7-day intervals, we observed a large reduction in whitefly adults, courting pairs, and nymph populations on eggplant leaves in a plastic greenhouse. 10) In the present study, we observed the effects of treatment with acetylated glyceride on the process of host selection behaviors and morphological characteristics of their labia and oviposition behaviors of B. tabaci adults. In addition, we evaluated the impact of the treatment on various developmental stages of B. tabaci in laboratory conditions.…”
Section: Introductionmentioning
confidence: 66%
“…We recently found that acetylated glyceride (acetic and fatty acid esters of glycerol), used as a plasticizer for chewing gum base (food additive), has a highly repellent effect and a courtship disruption effect on Mediterranean and Middle East-Asia Minor 1 (MEAM1, formerly B-biotype) B. tabaci adults without causing phytotoxicity to target crops or toxicity to beneficial insects (Kashima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%